Burnt shadows - Shamsie, Kamila (Bloomsbury London, 2009)
"August 9, 1945, Nagasaki. Hiroko Tanaka steps out onto her veranda, taking in the view of the terraced slopes leading up to the sky. Wrapped in a kimono with three black cranes swooping across the back, she is twenty-one, in love with the man she is to marry, Konrad Weiss. In a split second, the world turns white. In the next, it explodes with the sound of fire and the horror of realization. In the numbing aftermath of a bomb that obliterates everything she has known, all that remains are the bird-shaped burns on her back, an indelible reminder of the world she has lost."--The publisher